9z+5=11z-5

Simple and best practice solution for 9z+5=11z-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9z+5=11z-5 equation:


9z+5=11z-5

We simplify the equation to the form, which is simple to understand
9z+5=11z-5

We move all terms containing z to the left and all other terms to the right.
+9z-11z=-5-5

We simplify left and right side of the equation.
-2z=-10

We divide both sides of the equation by -2 to get z.
z=5

See similar equations:

| 10-4r=-2(3r+5)+7r | | 2x-x+6x+5=41 | | 5(-4)=-3x+44 | | -6(10+p)=-150 | | 20x-x^2-150=0 | | 10+6x-4=26+2x | | -7w+4=10 | | 8x+24+2x+96=180 | | -2n+4n-7=0 | | -12+x=-3 | | 3y-6=6(y-2) | | -5-4x-2x=-7 | | 12+3x-3=15-4x | | (12x^2)+x+4=0 | | 3(5x-7)=5(3x+4) | | 3x+6x-6=18 | | 4x+4+2x+38=180 | | 4z-13=3 | | 2x+4=5(x+1)3-(x+2) | | 12x^4=18x^2 | | x-9y+7=0 | | 7x+2x-7=3 | | 10x-5.3=1.2 | | .5r+4=20 | | -63=-12.5t-4.9t^2 | | 4+6x-5=43 | | 4(b+5)=2(4b+5) | | x=x^2+23 | | y=-2+6x | | .8x-9=.4 | | -50=5x | | 6-4x+3=31 |

Equations solver categories